Against capital punishment : the anti-death penalty movement in America, 1972-1994 - Haines, Herbert H. (Oxford University Press, 1999)
While most western democracies have renounced the death penalty, capital punishment has growing support in the United States. A significant and vocal minority continues to oppose it. This is an account of anti-death penalty activism in America since the ten-year moratorium on executions ended.